Firm Ownership Control and Management Practices, with an Update on Sub-Saharan Africa - Andrew Dabalen; Saumik Paul (Institute of Labor Economics (IZA), 2024)
This paper examines if ownership control - the share of largest owner in the firm - explains the difference in the adoption of management best practices between Sub-Saharan Africa (SSA) and rest-of-the-world (ROW). Using a sample of 156,833 firms from 130 countries, of which 25,005 are in SSA, we estimate the average management practices score in SSA and ROW as -0.096 and 0.023, respectively. The average treatment effect on management practices scores of going from less than 50 percent ownership control to full ownership control is negative, and it is comparable between SSA (-0.136) and ROW (-0.147). However, the share of sole proprietorships characterized by full ownership control is 52 percent in SSA compared to only 30 percent in ROW. A lower average of management practices score in SSA compared to ROW is largely driven by preponderance of sole proprietorship, in addition to lack of awareness about management best practices in SSA.
Keywords: D24; E25; G31; L11; O30; O47; 330; business practices; productivity; management; Sub-Saharan Africa